Root application of Bisphenol A (BPA) and di(2-ethylhexyl) phthalate (DEHP) at environmental doses impacts tomato growth and production - Nina Durand; Johanna Rivas; Annick Maria; Annabelle Fuentes; Emilie Crilat; David Siaussat; Arnould Savouré; Cécile Cabassa (PLoS ONE, 2025)
The escalating decline in biodiversity in agroecosystems is a growing concern. Chemical pollutants such as plasticizers are increasingly implicated in this decline, with potential implications for both food production and quality. Among these pollutants, the endocrine-disrupting compounds (EDC) bisphenol A (BPA) and di(2-ethylhexyl) phthalate (DEHP) are particularly widespread and well documented in agricultural environments. Previous studies have reported the bioaccumulation of BPA and DEHP in crop plants, resulting in impaired growth and productivity. However, these findings were based on contaminant concentrations thousands of times exceeding those typically found in the environment. This raised critical questions about the real effects of BPA and DEHP on crop plants at environmentally relevant doses, particularly under conditions of single or combined exposure. This study investigated the effects of environmental doses of BPA and DEHP on tomato plants (Solanum lycopersicum), one of the most important crops in the world. Plants were exposed via root application to low and intermediate environmental concentrations (0.05 µg.L-1 BPA and 0.5 µg.L-1 DEHP or 50 µg.L-1 BPA and 10 µg.L-1 DEHP, respectively), under both mono- and co-exposure. The results revealed disruption in plant growth and productivity, which varied based on the specific EDC, concentration and exposure conditions.